THE INFLUENCE OF STUDYING THE BOOK OF SYIFAUL JINAN ON THE LEARNING OUTCOMES OF AL-QUR'AN AND HADITH STUDENTS AT MTS NEGERI 2 WONOSOBO - Betari Sabdo Bumi; Nasokah; Abdul Majid (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2026)
This research is motivated by the importance of the ability to read the Qur'an according to the rules of tajwid in supporting the success of learning the Qur'an and Hadith. However, there are still differences in reading ability between students who attend Islamic boarding schools and those who do not. The study of the book Syifaul Jinan as a basic book of tajwid science is thought to have contributed to improving this ability. This study aims to: (1) determine the learning model of the book Syifaul Jinan, (2) analyze its influence on the learning outcomes of the Qur'an and Hadith, and (3) identify its benefits for students. This study uses a quantitative approach with a comparative type. The research sample was 171 students of grade 1 MTs Negeri 2 Wonosobo consisting of boarding and non-boarding students. Data collection techniques include observation, interviews, and documentation. Data analysis was carried out through normality tests, homogeneity tests, and hypothesis tests using the Independent Sample t-test. The results of the study show that: (1) the learning model uses the bandongan and sorogan methods which are structured and applicable; (2) there is a significant influence of studying the book Syifaul Jinan on the learning outcomes of the Qur'an and Hadith (Sig. 0.000 < 0.05) with an average difference of 16.56 points; and (3) studying the book provides benefits in the cognitive, affective, and psychomotor aspects, especially in improving the ability to read the Qur'an fluently and tartil.